2013
DOI: 10.1089/ten.tea.2012.0391
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Promote Angiogenesis and Tissue Formation for In Vivo Tissue Engineering

Abstract: Adult mesenchymal stem cells secrete a variety of angiogenic cytokines and growth factors, so we proposed that these paracrine mechanisms may be used to promote vascularization and growth for tissue engineering in vivo. We tested whether or not human adipose-derived stem cells (ASCs) promote tissue formation in rats. ASCs were evaluated in vitro for mRNA expression of angiogenic factors, including the vascular endothelial growth factor, basic fibroblast growth factor, interleukin-8 (IL-8), and stromal cell-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 55 publications
1
68
0
2
Order By: Relevance
“…Our results showing an increased amount of RECA-1-positive staining in conduits supplemented with stem cells could be attributed to the high levels of VEGF and angiopoietin secreted by the stem cells. Other very recent studies have indicated that human ASC used in animal experimental models can promote tissue formation and enhance graft retention as a result of enhanced vascularity [77,78].…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 99%
“…Our results showing an increased amount of RECA-1-positive staining in conduits supplemented with stem cells could be attributed to the high levels of VEGF and angiopoietin secreted by the stem cells. Other very recent studies have indicated that human ASC used in animal experimental models can promote tissue formation and enhance graft retention as a result of enhanced vascularity [77,78].…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 99%
“…This heterogeneous population of isolated multipotent stem cells, endothelial cells, pericytes and haematopoietic cells has been shown to assemble into microvascular networks when seeded onto different scaffold types Güven et al, 2011;Laschke et al, 2013;Klar et al, 2014). Moreover, the cells promote angiogenesis and vessel maturation by secreting various pro-angiogenic and regulatory proteins (Matsuda et al, 2013;Rohringer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…AKMKH'lerin yeni epidermis oluşmasında, cilt yaşlanmasının engellenmesinde, anjiogenezisin hızlandırılmasında ve fibroblastların proliferasyonunda olumlu etkileri gösterilmiştir. 35,36 Sıçanlar üzerinde yapılan bir çalışmada, yara yü-zeyine uygulanan kök hücre ekilmiş farklı biyomateryallerin kök Hücre ekilmeden uygulanan gruplara göre epitelyal kalınlıkta ve ortalama kıl folikülü sayılarında anlamlı derecede farklı-lık izlenirken, kollajen deposunun diğer gruplara göre anlamlı olarak oldukça az olduğu gösteril-miştir. 37 Biyomateryaller üzerine ekilen AKMKH'lerin fibrovasküler, endotelyal ve epitelyal dokuların diferansiasyonuna olanak sağla-dığı için otolog deri grefti yapımında sıklıkla başvurulan kök hücre kaynağı olabileceği düşü-nülmektedir.…”
Section: Burun Ci̇ldi̇unclassified